ORIENTASI INKLUSIF DAN KEHARMONISAN PASANGAN PERKAWINAN BEDA GEREJA DI PAROKI SANTO IGNATIUS, LAHA - Sirait, Aprillia Ona Medica (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2021)
This research aims to delve deeper into how to manage religious belief different churches so that it does not disrupt household harmony, to identify concrete steps taken to strengthen emotional and spiritual connections between couples in the context of religious differences, and to understand the process of integrating and appreciating each partner’s religious traditions and values to create an inclusive and harmonious household environment. This research collection conducted via observation and interviews. This research found that interdenominational marriage is a phenomenon that occurs in society. Marriage involves two individuals from different religious backgrounds, namely Protestantism and Catholicism. Such a marriage provides a religious perspective to the family to accept and respect each other, build open dialogue, have a strong commitment to maintaining family harmony, support one another in religious duties and services, and also provide education and shared learning, create new family traditions, and instill respect and tolerance. Thus, family harmony between different churches can be created and sustained if there is mutual acceptance. The theological orientation used in this marriage practice aligns with an inclusive orientation which involves recognition of other religions, openness and acceptance, and does not require changing the other person’s religious beliefs.